An Assessment on the Disaster Risk Reduction Knowledge Among School Students: A study on Public Schools at Kathmandu - Duwadi, Pampha (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
Nepal faces a lot of natural disasters, like landslides and floods time and again. These disasters cause a big loss of property for the country each year. Many people also get physically hurt, and houses and other buildings and many other properties get damaged. This has happened because people more often don't know how to stay safe during disasters. It seems that Nepal remains unprepared to prevent these disasters from happening or lessen their impact. Some programs and activities are conducted by the government to help people affected from disasters, but it is found largely insufficient and inappropriately implemented. Similarly it is found that different levels of the government don’t cooperate to each other while working in situation. In this study, researcher aims to study the understanding of school students about reducing the risks of disasters. Methodologically, this research has been based on qualitative in nature. Questionnaire method was executed as data collection tool. Total 30 students from different classes were selected as sampled respondents using purposive sampling method from two different government schools in Kathmandu-16. The results showed that majority, (more than 70 percent) of the students are well known about the safety rules set by the government for schools in Nepal. It shows that many students are enough aware and educated about how to stay safe during disasters. But still considerable number of students is found unaware about the disaster risk reduction knowledge. This research also found some problems about the teaching process of disaster risk reduction in schools. The findings may also help government agencies working on disaster risk reduction in Nepal to improve their programs for schools.